Hannah Arendt, Leo Strauss e o estatuto do problema da normatividade na teoria política - Hugo Araújo Prado (2019)
The aim of this dissertation is to investigate the status of the problem of normativity on the light of Hannah Arendts and Leo Strauss thoughts. This problem is explained by the following questions: what are political norms?; in which terms can we describe the attribute of this norms: to inspire or to orientate action? In present times is possible to add the question: this problems are still valid to political theory and political philosophy? I shall argue that the concepts of natality and plurality, developed by Hannah Arendt, and the question on the best regime, revitalized by Leo Strauss, allow us, on the one hand, to reconsider the conceptual status adquired by the problem of normativity in the tradition of political philosophy and in contemporary political thought. On the other hand, these are non-reconcilable solutions regarding the relationship between the realm of theory and the normative realm, the attribute of normative principles, and their positions about the relationship between political form, normativity, and modernity.